ANTI-ULCER ACTIVITY OF DIFFERENT EXTRACT OF KIGELIA PINNATA IN EXPERIMENTAL ANIMALS - RAJASEKARAN.S (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Kigelia pinnata (Bignoniaceae) has been extensively used in medicine for the treatment of ulcer. Hence, the present study was intended to evaluate total Chloroform, Diethylether and ethanolic leaf extracts of Kigelia pinnata for peptic ulcer activities. Methods: The Peptic ulcer activity was studied by Indomethacin, Alcohol and pyloric ligation models experimentally induced ulcer. Acute toxicity study and preliminary phytochemical screening were also studied to evaluate the toxicity Results: No toxicity profile was observed in rats after oral administration of the different extracts at the dose of 2g/kg body weight. The different extracts at a dose of 100 mg/kg and 200 mg/kg administered with the extracts of Kigelia pinnata there was significant (P < 0.001) reduction in volume of gastric acid secretion, PH, free acidity, total acidity and ulcer index with respect to control. Phytochemical screening of the plant extract revealed the presence of tannins, alkaloids, flavonoids and saponins, and terpenoids. Conclusion: It can be concluded that the anti-ulcer activity elucidated by Kigelia pinnata could be mainly due to the modulation of defensive factors through an improvement of gastric cytoprotection and partly due to acid inhibition. Keywords: Kigelia pinnata, Indomethacin, Alcohol, pyloric ligation, anti-ulcerogenic